Pemanfaatan minyak jelantah menjadi pengharum ruangan sebagai peluang usaha masyarakat di Kecamatan Senapelan - Hafid Muhaimin Hasward; Zulkarnain Zulkarnain; Manyuk Fauzi (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2021)
Used cooking oil is used frying oil that is usually used repeatedly. For fried food and rice traders, using used cooking oil repeatedly can get big profits because it can save expenses to buy cooking oil. Cooking oil is used repeatedly, causing the fatty acids contained will be more saturated and will change color. dumping used cooking oil into the trenches around the place of sale can damage existing ecosystems and kill aquatic biota and siltation of trenches. If used cooking oil is processed and utilized, it can be an added value and a business opportunity for the community. Like the research conducted by Dalimunthe (2009) turned waste cooking oil into soap. Based on the results of research traders in the District Senapelan know the dangers arising from waste cooking oil is very large for consumers and the environment, but all traders still use cooking oil more than four times the frying pan. Cooking oil used as a frying oil besides being used as soap can also be reused as an air freshener. The need for the government's role in increasing the knowledge of traders to preserve the environment that can be generated from waste cooking oil.